The use of herbal medicines in patients with type-2 diabetes mellitus in Indonesia - Utomo, Astika Widy; Annisaa, Eva; Antari, Arlita Leniseptaria; Armalina, Desy (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2022)
In Indonesia, the use of herbal medicine as an alternative medicine is increasing. Herbal remedies are used as complementary medicine and self-medication. Diabetes mellitus requires treatment over the long term. This may contribute to the medication adherence problem. Consequently, many patients seek alternative treatments, such as herbal medications. The purpose of this study was to determine the use and type of herbal medicines among diabetic patients in Indonesia. A cross-sectional study with 190 respondents selected at random from multiple cities in Indonesia. A questionnaire was used to determine the most frequently used herbal medicine, the demographic profile of the patients, the health services, and the level of patient satisfaction with the use of herbal medicines. The participants were predominantly female (62.7%), housewives (39.5%), aged between 40 and 65 (84.5%), high school graduates (74.7%), and had low to moderate incomes (74.7%). The use of herbal medicine was 22%, and the combination of herbal medicine and prescription medication was 6%. Bitter leaves (10%), mangosteen peel (8.9%), insulin leaves (7.9%), mahkota dewa herbs (6.3%), and bitter melon are used as herbal or traditional medicines (4.7%). In terms of satisfaction, 28.7%, 40.9%, and 14.4% of respondents were quite satisfied, satisfied, and very satisfied with the use of herbal medicines, respectively. Herbal remedies are commonly used in alternative diabetes treatments. Bitter leaves are the most frequently used herb, with over half of respondents expressing satisfaction with the benefits of herbal medicine.